Adaptive Speaking Performance Training: Enhancing Communication Readiness of Hospitality Students in the Industry 4.0 Era - Muhammad Bambang Purwanto; Issy Yuliasri; Widhiyanto; Fahrur Rozi (Universitas Pendidikan Ganesha, 2025)
The rapid digital transformation of the hospitality industry requires graduates who are not only linguistically competent but also confident and adaptive in digital communication. However, many students remain insufficiently prepared to meet communication demands in professional contexts. This study aims to evaluate the effectiveness of Adaptive Speaking Performance Training in enhancing hospitality students’ communication readiness. Employing a quasi-experimental one-group pretest–posttest design, the study involved 35 sixth-semester students from the English for Business and Professional Communication program. Data were collected using a validated speaking performance rubric (α = 0.87; inter-rater reliability r > 0.85), a digital communication readiness questionnaire, and semi-structured interviews. Quantitative data were analyzed using paired-sample t-tests, while qualitative data were examined through thematic analysis. The results reveal statistically significant improvements (p < 0.001) across all speaking performance dimensions, with the greatest gains observed in self-confidence (+2.77) and interactive communication (+2.26). Students also reported substantially higher levels of readiness to engage in digital professional environments. The study concludes that simulation-based and contextual training effectively bridges the gap between academic learning and industry demands. These findings support the integration of task-based, digitally supported speaking training into vocational curricula as a scalable model for preparing the future hospitality workforce in the Industry 4.0 era.